Thermodynamic Analysis of Heat and Fluid Flow in a Microchannel With Internal Fins - Narayanaswamy, Ramesh; Chandratilleke, Tilak; Foong, Andrew Jun Li (ASME, 2009)
Efficient cooling techniques are one of the critical design requirements for maintaining reliable operational characteristics of modern, miniaturised high performance electronic components. Microchannel heat sinks form an integral part of most devices used for thermal management in electronic equipment cooling. A microchannel of square cross section, having internal longitudinal fins is considered for analysis. A numerical study is carried out to investigate the fluid flow and heat transfer characteristics. Three-dimensional numerical simulations are performed on the microchannel in the presence of a hydrodynamically developed, thermally developing laminar flow. Further on, a thermodynamic analysis is carried out, for a range of fin heights and thermophysical parameters, in order to obtain the irreversibilities due to heat transfer and fluid flow within the microchannel. An optimum fin height, corresponding to the thermodynamically optimum conditions that minimize the entropy generation rates has been obtained. The effect of the presence of internal fins on the entropy generated due to heat transfer, fluid friction, and the total entropy generation is also provided.